Comparison of fretting behaviour of electrodeposited Zn-Ni and Cd coatings. (April 2018) - Lee, L.; Descartes, S.; Chromik, R.R.
Abstract: Zn-Ni is a primary replacement candidate for cadmium in the aerospace industry. However, tribological behaviours of these coatings are not well understood, despite the importance in their applications. This study compares the fretting behaviour of Zn-Ni and cadmium coatings, a hard and a soft coating. As the mechanical properties are different, coatings were compared under similar contact stresses and normal loads. Under similar contact stresses, Zn-Ni wore severely due to gross slip in the contact at high displacement amplitude. For cadmium, wear occurred through ejection of the coating from the contact, which became more severe when the displacement amplitude increased. Under similar normal loads, Zn-Ni remained in the stick regime and there was minor wear in the contact. Highlights: Fretting behaviour of Zn-Ni and Cd coatings studied and compared. The main wear mechanism for Cd is ejection of coating material through plastic flow. At high load, Zn-Ni remained in the stick regime and there was minor wear. At low load, when gross slip occurred in the contact for Zn-Ni severe wear occurred.